2018
DOI: 10.3389/fmicb.2018.01938
|View full text |Cite
|
Sign up to set email alerts
|

Further Spread of a blaKPC-Harboring Untypeable Plasmid in Enterobacteriaceae in China

Abstract: The wide spread of Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacteriaceae is great threat to public health in China. Plasmids are among the major factors mediating blaKPC gene dissemination. A total of 156 carbapenem-resistant Enterobacteriaceae (CRE) isolates were identified in a tertiary hospital in China. Six KPC-producing isolates, namely, E. coli (n = 2), E. asburiae (n = 1), C. freundii (n = 1), C. portucalensis (n = 1), and C. koseri (n = 1), tested positive for the pCKPC18-1-like untype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…portucalensis ( n = 6), and C. europaeus ( n = 2) (Figure 1). To the best of our knowledge, this is the first report on the isolation of C. portucalensis and C. europaeus strains from animals, although these species have been rarely reported in humans [26,27]. These findings imply the prevalence of several Citrobacter species in companion animals, in addition to C. freundii .…”
Section: Resultsmentioning
confidence: 74%
“…portucalensis ( n = 6), and C. europaeus ( n = 2) (Figure 1). To the best of our knowledge, this is the first report on the isolation of C. portucalensis and C. europaeus strains from animals, although these species have been rarely reported in humans [26,27]. These findings imply the prevalence of several Citrobacter species in companion animals, in addition to C. freundii .…”
Section: Resultsmentioning
confidence: 74%
“…However, except for TZP and ATM, the IPM, MEM, FEP, and CAZ MICs for CTB were higher than that for Tn4401B but lower than that for Tn4401A. In addition, previous studies have shown that the ertapenem and FEP MICs for the E. coli transformants bearing wild-type plasmids with the Tn3-Tn4401 chimera were the same as those for the corresponding strains trans- formed with plasmids containing Tn4401a but were much higher than those for the transformants containing Tn4401b or Tn4401h (12,20). Further evaluation revealed that the bla KPC mRNA expression of Tn4401A was 3-fold (P Ͻ 0.01) higher than that of Tn4401B, which is consistent with the results of a previous study (17).…”
Section: Discussionmentioning
confidence: 73%
“…Bacterial species were initially identified with the VITEK2 Compact system (bioMérieux Vitek, USA) and further confirmed by the automated mass spectrometry microbial identification system (matrix-assisted laser desorption ionization-time of flight [MALDI-TOF]; Bruker, USA). Genetic environments of the bla KPC gene were initially detected by PCR with specific primers described in our previous study (20) and further confirmed by Sanger sequencing. DNA fragments containing the promoter region and bla KPC gene (complement sequence corresponding to positions 19105 to 21715 of pKP048 [16]) were amplified and cloned into pET28X (a modified pET28a vector with T7 promoter deletion [ Fig.…”
Section: Antimicrobial Agents and Chemotherapymentioning
confidence: 99%
“…has been confirmed in Shandong, Zhejiang, Taiwan, and other provinces. [33][34][35] KPC-2 was the most important in K. pneumoniae, whereas NDM-1 was the most important in E. coli. Notably, in previous studies in China, a few strains of E. coli with KPC-2 were detected.…”
Section: Discussionmentioning
confidence: 98%